2020
DOI: 10.1371/journal.pone.0234648
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil moisture levels on the growth and reproductive behaviour of Avena fatua and Avena ludoviciana

Abstract: Adaptation of weeds to water stress could result in the broader distribution, and make weed control task increasingly difficult. Therefore, a clear understanding of the biology of weeds under water stress could assist in the development of sustainable weed management strategies. Avena fatua (wild oat) and A. ludoviciana (sterile oat) are problematic weeds in Australian winter crops. The objectives of this study were to determine the growth and reproductive behaviour of A. fatua and A. ludoviciana at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…Plants under no water stress (100% SWC) had the maximum shoot biomass (23 g plant -1 ) and root biomass (5 g plant -1 ). Similar findings were reported for jungle rice, itchgrass, wild oat, sterile oat, and common waterhemp (Chauhan 2013;Chauhan and Johnson 2010;Sahil et al 2020;Sarangi et al 2015). Approximately 85% and 68% reduction in shoot biomass was recorded at 12.5% and 25% SWC, respectively, relative to 100% SWC.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Plants under no water stress (100% SWC) had the maximum shoot biomass (23 g plant -1 ) and root biomass (5 g plant -1 ). Similar findings were reported for jungle rice, itchgrass, wild oat, sterile oat, and common waterhemp (Chauhan 2013;Chauhan and Johnson 2010;Sahil et al 2020;Sarangi et al 2015). Approximately 85% and 68% reduction in shoot biomass was recorded at 12.5% and 25% SWC, respectively, relative to 100% SWC.…”
Section: Resultssupporting
confidence: 83%
“…Clayton], although growth and seed production decreased with increasing water stress, both were lower at 100% than at 75% field capacity (Chauhan 2013). Growth and reproductive behavior of wild oat (Avena fatua L.) and sterile oat (A. ludoviciana L.) decreased with increasing water stress (Sahil et al 2020). Bengal dayflower (Commelina benghalensis L.), spiny amaranth (Amaranthus spinosus L.), and Chinese sprangletop [Leptochloa chinensis (L.) Nees] have also been reported to have the ability to produce shoot biomass and reproduce under water stress (Chauhan and Abugho 2013;Webster and Grey 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is a wild oat that is widespread all over the world, growing in various climatic zones from the tropics to the polar circle. A. fatua is considered to be one of the worst annual weeds in temperate zone cereals [ 28 , 29 ], causing enormous problems in agriculture [ 30 , 31 , 32 , 33 ]. Loskutov and Rines [ 1 ] have concluded that this species is a source of resistance to various oat diseases.…”
Section: Introductionmentioning
confidence: 99%
“…High infestations of A. ludoviciana in winter season crops could be due to its favourable biological attributes (Mahajan and Chauhan 2021a). For example, high seed-shattering ability, adaptation to a wide range of temperatures and water stress for germination and growth, and innate dormancy in seeds are some of the attributes that make A. ludoviciana emerge at different periods of crop seasons (Sahil et al 2020;Mahajan and Chauhan 2021c). Emergence pattern studies indicate the potential of A. ludoviciana to emerge from March to October (autumn, winter, and spring) in eastern Australia (Mahajan and Chauhan 2021b).…”
Section: Introductionmentioning
confidence: 99%